Study On Government Policy In Managing The Corona Disease Virus Pandemi 2019 (Covid-19) In Indonesia - Budiman; Imam Budi Santoso; Holyness N. Singadimedja (IHSA Institute, 2021)
The current development of the Covid-19 pandemic is very worrying where there is an increase in special corona cases in Indonesia. This study aims to identify and analyze the policies taken by the government in handling the Covid-19 pandemic and the steps taken by the government to mitigate the impacts, especially the economic and social impacts of the Covid-19 pandemic. The legal research method used is the normative legal research method. The approach used in this research is a statutory approach and a conceptual approach. This research is based on the legislation governing the handling and handling of the Covid-19 pandemic as well as an analysis of the concept of establishing these laws and regulations. The results of this study are in the context of handling Covid-19, starting with the government issuing a policy on Large-Scale Social Restrictions which refers to Law Number 6 of 2018 concerning Health Quarantine. The implementing regulations are Government Regulation Number 21 of 2020 concerning Large-Scale Social Restrictions, as well as the Presidential Decree on Health Emergencies. Until now, the government has issued a PPKM policy which is carried out regularly. To address the economic and social impact of Covid-19, the government has taken several policies, including: Regulation of the Minister of Finance of the Republic of Indonesia Number 23/Pmk.03/2020 concerning Tax Incentives for Taxpayers Affected by the Coona Virus Outbreak; Regulation of the Financial Services Authority of the Republic of Indonesia Number 11 /Pojk.03/2020 concerning National Economic Stimulus as a Countercyclical Policy for the Impact of the Spread of Corona Virus Disease2019; and Instruction of the President of the Republic of Indonesia Number 4 of 2020 concerning Refocussing of Activities, Reallocation of Budgets, and Procurement of Goods and Services in the Context of Accelerating Handling of Corona Virus Disease 2019 (Covid-19).